Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Pemahaman Dan Komunikasi Matematik Mahasiswa - Cipta, Eliva Sukma (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
The aim of this study was to examine the improvement and achievement of mathematical understanding and mathematical communication skills of better among students who earn the PBL and the conventional learning, in terms of overall and category of early mathematics ability students (high, medium, low), student attitudes toward the PBL. The method used is an experimental method to the study design pretest-posttest control group. Research subjects involving 73 students Semester VI Mathematics Education courses UIN Bandung. The results of this study are: 1) there is a significant difference in improvement between the mathematical understanding students studying with PBL and conventional learning; 2) there is no significant difference between the increase in mathematical understanding students studying with PBL and conventional learning in terms of mathematical communication students; 3) there is no significant difference in improvement between the mathematical communication students studying with PBL and conventional learning; 4) there is no significant difference between the increase in mathematical communication students studying with PBL and conventional learning in terms category of early mathematics ability students; 5) the students have a positive attitude towards learning mathematics with PBL.